The impact of educational exercises utilizing the McCarthy model on attention and the learning of some forward and backward rolls on the floor exercise mat in artistic gymnastics for female students - Abeer Ali Hussein (Eximia, 2025)
Learning is a branch of general scientific and educational knowledge that governs an individual's life from birth to death. Because of its direct and fundamental relationship to motor control, motor learning is regarded as one of the science's most significant in the fields of physical education and sports sciences. The educational process is a series of continuous variables in the relationship between the teacher and the learner, which in turn helps in acquiring experiences and knowledge to bring about various behavioral changes. Additionally, guiding learners to think aloud encourages them and instills in them the desire to reach the maximum benefit allowed by their abilities. Furthermore, it drives and motivates them to practice thinking processes and skills, as well as develop concepts and cognitive structures and correct misconceptions through the processes of assimilation and accommodation. Among educational constructivist models, the McCarthy model emerged as a constructivist philosophy model based on the learner's understanding and interpretation of the phenomena they encounter, as well as their ability to assimilate it in light of previous learning experiences and the transfer of training effects. The research problem is formed around the fact that some teachers still impose a teaching style on students without considering their preferences for one style or another. Since inclination and desire for application and learning are fundamental to learning motor skills in gymnastics, it has become essential for teachers to understand their students' preferences for teaching styles in order to increase the effectiveness of positive participation in the lesson. The researcher attributes the study of this phenomenon and the exploration of its true reality through the use of a method different from the conventional approach in expressing performance in improving attention and learning some basic skills on the floor exercise in gymnastics for third-year students at the College of Physical Education and Sports Sciences. The aim of the research is to identify the preferential impact on improving attention and learning the skills of forward and backward rolls on the floor exercise in gymnastics between the educational curriculum using the McCarthy model and the curriculum adopted by the teacher.